Comparative Remineralization Efficacy of Topical NovaMin and Fluoride on Incipient Enamel Lesions in Primary Teeth: Scanning Electron Microscope and Vickers Microhardness Evaluation - Shihabi, Safaa; AlNesser, Salma; Comisi, John C. (European Journal of Dentistry, 2020)
Objective Evaluating the potential remineralization effect of NovaMin prophylaxis paste on artificial enamel lesions in primary teeth using Vickers microhardness and scanning electron microscope.Materials and Methods Forty sound buccal and lingual surfaces of human primary canine teeth were randomly divided into two groups after creating artificially demineralized lesions (G1: NovaMin and G2: fluoride; 20 per group) and then treated with the respective remineralization agents. The remineralization cycle repeated twice daily for 10 days. The groups were evaluated with Vickers microhardness and scanning electron microscope before and after de/remineralization.Results Statistically significant difference of microhardness was observed between demineralized enamel and remineralized enamel with group 1 and group 2 (p = 0.000 and p = 0.000, respectively). No statistically significant difference of microhardness was observed between two remineralized agents (p = 0.368).Conclusion Within the limitation of this in vitro study, NovaMin enhances the remineralization process equally to fluoride.
Keywords: fluoride; NovaMin; vickers surface microhardness; scanning electron microscope; white spot lesions; hydroxycarbonate apatite